Accessing and Improving Testing, Calibration and Validation Management of Hospital Equipment in Nepal - Karna, Pawan Kumar; Jain, P. J. (A Bi-annual South Asian Journal of Research & Innovation, 2024)
This article has examined the current state of testing, calibration, and validation (TCV) management of hospital equipment in Nepal. It has highlighted the role these processes play in ensuring patient safety and healthcare quality. Nepal faces numerous challenges in managing medical devices, including resource limitations, insufficient training, and lack of standard regulatory frameworks. These issues, particularly in rural and under-resourced healthcare facilities, lead to inconsistent equipment performance and increased risks to patient safety. Through a detailed literature review and field-based analysis, the study compares Nepal TCV practices with global standards. It is identified key gaps and opportunities for improvement. Findings exposed that while some urban hospitals have access to modern equipment and trained personnel. Rest many rural facilities lack the necessary infrastructure and expertise to maintain reliable medical devices. The study emphasized the need for a national regulatory body, enhanced training programs for biomedical technicians, and improved access to advanced calibration technologies. Drawing on international best practices, the article recommends policy reforms, investments in technical capacity building, and further research to create a more robust and standardized TCV system in Nepal.